Identification of Small Molecule Compounds for Pharmacological Chaperone Therapy of Aspartylglucosaminuria - Banning, Antje; Gülec, Christina; Rouvinen, Juha; Gray, Steven J.; Tikkanen, Ritva; Justus Liebig University Giessen (My University, 2016)
Aspartylglucosaminuria (AGU) is a lysosomal storage disorder that is caused by genetic deficiency of the enzyme aspartylglucosaminidase (AGA) which is involved in glycoprotein degradation. AGU is a progressive disorder that results in severe mental retardation in early adulthood. No curative therapy is currently available for AGU. We have here characterized the consequences of a novel AGU mutation that results in Thr122Lys exchange in AGA, and compared this mutant form to one carrying the worldwide most common AGU mutation, AGU-Fin. We show that T122K mutated AGA is expressed in normal amounts and localized in lysosomes, but exhibits low AGA activity due to impaired processing of the precursor molecule into subunits. Coexpression of T122K with wildtype AGA results in processing of the precursor into subunits, implicating that the mutation causes a local misfolding that prevents the precursor from becoming processed. Similar data were obtained for the AGU-Fin mutant polypeptide. We have here also identified small chemical compounds that function as chemical or pharmacological chaperones for the mutant AGA. Treatment of patient fibroblasts with these compounds results in increased AGA activity and processing, implicating that these substances may be suitable for chaperone mediated therapy for AGU.
Keywords: ddc:610